Changing Photographic Landscape. - John Boyd
Digital photography continued to dominate the camera business in 2006 with about 73 million digital units delivered globally compared to just over a million units of film cameras. Compounding the woes of traditional camera makers is the entry of consumer electronics companies such as Casio Computer, Matsushita Electric Industrial, Samsung Electronics, and Sony, who bring innovative design and new features to their cameras such as antishake systems and automated zoom lenses now found on even the smallest cameras. With so many companies now crowding the market, it shouldn't come as a surprise that manufacturers who are unable to adapt quickly enough or to compete in producing vital electronic components will drop their film businesses and sell much of their remaining operations
Keywords: Antishake systems; Automated zoom lenses; Camera business; Camera makers; Consumer electronics companies; Design innovation; Digital photography